1995
DOI: 10.1530/eje.0.1330038
|View full text |Cite
|
Sign up to set email alerts
|

Technetium-99m pentavalent dimercaptosuccinic acid imaging in patients with pituitary adenomas

Abstract: We studied the tumor-seeking agent technetium-99m-labeled pentavalent dimercaptosuccinic acid ([99mTc](V)DMSA) to visualize 21 growth hormone (GH)-, nine prolactin (PRL)-, two mixed GH/PRL-, six adrenocorticotrophin (ACTH)-secreting and 15 clinically non-functioning pituitary adenomas, three craniopharyngiomas and one dysgerminoma of the sella. All non-adenomas and 31 out of 53 adenomas were studied before treatment: 22 after surgery and/or radiotherapy. Eight cases of acromegaly were studied before and after … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
10
0
1

Year Published

1999
1999
2019
2019

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 9 publications
3
10
0
1
Order By: Relevance
“…9) In our series, marked diffuse accumulations of 99m Tc(V)-DMSA were observed in 17 of 21 patients with pituitary adenomas, especially seven of seven non-functioning adenomas, but not in patients with non-pituitary adenomas. These results suggest that 99m Tc(V)-DMSA can visualize pituitary adenomas clearly, and diffuse accumulation of 99m Tc(V)-DMSA could differentiate non-functioning adenoma from non-pituitary adenomas using only the planar image.…”
Section: Discussionsupporting
confidence: 40%
See 2 more Smart Citations
“…9) In our series, marked diffuse accumulations of 99m Tc(V)-DMSA were observed in 17 of 21 patients with pituitary adenomas, especially seven of seven non-functioning adenomas, but not in patients with non-pituitary adenomas. These results suggest that 99m Tc(V)-DMSA can visualize pituitary adenomas clearly, and diffuse accumulation of 99m Tc(V)-DMSA could differentiate non-functioning adenoma from non-pituitary adenomas using only the planar image.…”
Section: Discussionsupporting
confidence: 40%
“…14) However, 99m Tc(V)-DMSA may accumulate only in endocrinological`u nbalanced'' pituitary glands. 9) In our series, no The neuroimaging characteristics of lesions are based primarily on the density differences and extravasation of contrast material in CT and differences in water content and water binding in MR imaging. 1) These features that control the signal intensity are frequently similar in various types of tumors, so the differential diagnosis is more often based on anatomical relationships, such as the deformation of adjacent structures.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…Purity and radiochemical quality controls demonstrated that over 98% of injectable preparations was 99m Tc(V)DMSA; less than 1% was, respectively, 99m Tc(III)DMSA or free 99m Tc pertechnetate. In fact, in early and in late images, the thyroid and gastric mucosa, which have avid uptake of free‐pertechnetate, were not visualized (Lastoria et al ., 1996).…”
Section: Methodsmentioning
confidence: 99%
“…In a previous study (Lastoria et al ., 1995), we reported that technetium‐99m pentavalent dimercaptosuccinic acid [ 99m Tc(V)DMSA], a tumour seeking agent previously shown to detect medullary thyroid cancer (Ohta et al ., 1984), head and neck squamous tumours (Watkinson et al ., 1989) and skeletal lesions from breast cancer (Kashyap et al ., 1992), was significantly concentrated in the majority of pituitary adenomas (up to 93% of those greater than 10 mm in size). The uptake of 99m Tc(V)DMSA was similar in untreated and surgically treated adenomas while it was significantly reduced after radiotherapy (Lastoria et al ., 1996).…”
mentioning
confidence: 99%